Cope children's anxious behavior and pain with virtual reality during venipuncture procedure in emergency department - Permaida, Permaida; Rustina, Yeni; Effendi, Defi; Nurlaelah, Siti (Intelektual Pustaka Media Utama, 2023)
Venipuncture procedures undeniably increase anxiety behavior and pain while children are in the emergency department. This study aimed to analyze the effectiveness of virtual reality (VR) on anxiety behavior and pain with the Dorothy-behavior theory during the venipuncture procedures procedure in the emergency department. The research used a quasi-experimental two-group pretest-posttest design with a control group design with 42 respondents in the yellow zone of the emergency department of RSPUN Cipto Mangunkusumo. Data analysis used the Wilcoxon test, Mann-Whitney, and ordinal regression. There were significant differences and comparisons between anxiety behavior (p-value <0.001) and pain (p-value <0.001) when the venipuncture procedure was performed in the experimental group. School-age children (p-value 0.026; OR=4.958) affect pain. This study recommends that nurses in emergency departments provide VR during venipuncture procedures to address anxiety and pain behaviors. In addition, Dorothy's behavioral theory in the vein puncture procedure has become an innovation in nursing care. Provide aspects of protection based on the age, gender, and experience of the child; maintenance aspects by looking at VR effects; and aspects of stimulation as reference materials or recommendations for further research on VR to overcome anxiety and painful behavior in children during venipuncture procedures.